Locally Enhanced Flow and Electric Fields Through a Tip Effect for Efficient Flow-Electrode Capacitive Deionization - Wang, Ziquan; Chen, Xiangfeng; Zhang, Yuan; Ma, Jie; Lin, Zhiqun; Abdelkader, Amor; Titirici, Maria‑Magdalena; Deng, Libo (Nano-Micro Letters, 2024)
Low-electrode capacitive deionization (FCDI) is an emerging desalination technology with great potential for removal and/or recycling ions from a range of waters. However, it still suffers from inefficient charge transfer and ion transport kinetics due to weak turbulence and low electric intensity in flow electrodes, both restricted by the current collectors. Herein, a new tip-array current collector (designated as T-CC) was developed to replace the conventional planar current collectors, which intensifies both the charge transfer and ion transport significantly. The effects of tip arrays on flow and electric fields were studied by both computational simulations and electrochemical impedance spectroscopy, which revealed the reduction of ion transport barrier, charge transport barrier and internal resistance. With the voltage increased from 1.0 to 1.5 and 2.0 V, the T-CC-based FCDI system (T-FCDI) exhibited average salt removal rates (ASRR) of 0.18, 0.50, and 0.89 μmol cm−2 min−1, respectively, which are 1.82, 2.65, and 2.48 folds higher than that of the conventional serpentine current collectors, and 1.48, 1.67, and 1.49 folds higher than that of the planar current collectors. Meanwhile, with the solid content in flow electrodes increased from 1 to 5 wt%, the ASRR for T-FCDI increased from 0.29 to 0.50 μmol cm−2 min−1, which are 1.70 and 1.67 folds higher than that of the planar current collectors. Additionally, a salt removal efficiency of 99.89% was achieved with T-FCDI and the charge efficiency remained above 95% after 24 h of operation, thus showing its superior long-term stability. Highlights: 1 Steel tip arrays were used as current collectors to replace planar conductors. 2 Optimal flow and electric fields reduced barriers for electron and ion transport. 3 Desalination performance of flow-electrode capacitive deionization is enhanced by the tip-array current collectors.